The Problem-Based Learning Model Assisted with the Ethlaf Application Contains Ethnomathematics to Improve Students' Conceptual Understanding Capability - Bintoro, Henry Suryo; Aulya, Richa; Wanabuliandari, Savitri (LPPM Undiksha, 2024)
Mathematics learning plays an important role in the world of education. However, the high demands for mastery of mathematics are not in accordance with current student learning outcomes. This is because learning is direct, so students' ability to understand concepts is low. This research aims to test the average ability of students to understand concepts by applying a problem-based learning model containing ethnomathematics supported by ETHLAF APPS, which is better than applying a direct learning model. This type of research is quantitative, using quasi-experimental methods and a nonequivalent pretest-posttest control group design. The sampling technique uses purposive sampling. This research was carried out in class X of Senior High School. The data collection technique uses tests, and the instrument uses concept understanding test questions. Data analysis includes the normality test, homogeneity test, similarity test, and final data analysis, namely the independent sample t-test. The research results show that the average ability of students to understand concepts when applying the problem-based learning model based on ethnomathematics assisted by ETHLAF APPS is better than when applying the direct learning model. This research concludes that students' ability to understand concepts using the ethnomathematics-based problem-based learning model supported by ETHLAF APPS is better than using direct learning. The ability to understand concepts is the main goal and important factor in learning mathematics.